Order Flow and Exchange Rate Dynamics in Continuous Time: New Evidence from Martingale Regression - Guo, Zi-Yi (International Journal of Economics and Financial Issues, 2017)
The so-called “foreign exchange rate determination puzzle” has been a hard topic in international finance for several decades. The puzzle illustrates the weak explanatory power of macroeconomic-based models of the nominal exchange rate fluctuations. We investigate the foreign exchange rate determination puzzle in a continuous-time framework. Following the market microstructure literature, a simple model of the determination of foreign exchange rates is developed, and the model concludes a result which is essentially a continuous-time version of the equation in Evans and Lyons (2002a). For estimation, we take an advantage of a newly-developed econometric tool based on a time change from calendar to volatility time. With this new estimation methodology, our results indicate that the effect of order flow on exchange rate is significantly improved compared with the traditional econometric tools. Keywords: Order Flow; Time-Change Sampling; Martingale Estimator JEL Classifications: C22; G15; G17